Polymerization kinetics of HEMA/DEGDMA: using changes in initiation and chain transfer rates to explore the effects of chain-length-dependent termination - Hacioglu, B; Berchtold, KA; Lovell, LG; Nie, J; Bowman, CN (Elsevier Sci Ltd, 2002)
The effect of kinetic chain length and chain transfer on the polymerization kinetics and network structure in polymerizations of loosely crosslinked 2-hydroxyethyl methacrylate/di(ethylene glycol) dimethacrylate mixtures was explored. Polymerization behavior of the monomer mixture in the presence and absence of a chain transfer agent was monitored at various initiation rates and chain transfer agent concentration levels. Dependence of the polymerization rate on the initiation rate was found to deviate from the classical square-root relationship because of chain-length-dependent termination. This effect was further confirmed by addition of a chain transfer agent. The presence of a chain transfer agent led to the formation of shorter kinetic chains, which enhanced termination and slowed the polymerization. Investigation of the polymerization kinetics after cessation of irradiation yielded k(t)/k(p)[M] values for both systems. Prior to the onset of reaction diffusion-controlled termination, the system that included a chain transfer agent exhibited much higher k(t)/k(p)[M] values than the polymerization system without added chain transfer agent. In addition, the onset of reaction diffusion-controlled termination was delayed to higher conversions in the system containing chain transfer agent. The impact of a chain transfer agent on the polymerization behavior and kinetics demonstrates that the chain-length-dependent termination phenomenon is indeed important and must be considered in kinetic modeling of loosely crosslinked systems. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: crosslinking photopolymerizations; chain-length-dependent termination (CLDT); (meth)acrylates; kinetics